Prevalence of Primary Open Angle Glaucoma in Patients with Myopia. - Archana Pushpakaran; Meenu C Jacob; Sedhu P.A; Cyriac Kurian (Asian Journal of Medical Research, 2019)
Background: Myopia is a condition of the eye that makes it difficult to see distant objects. The present study was conducted to assess prevalence of primary open angle glaucoma in patients with myopia. Subjects and Methods: This cross- sectional study was conducted in outpatient Department of Ophthalmology, Sree Narayana institute of Medical Sciences. A minimum of 100 patients with myopia were included in the study. Prevalence of primary open angle glaucoma in patients with myopia was recorded. Results: In right eye, patients with IOP between 8-21 is 84%, > 21 is 16%. In left eye, patients with IOP between 8-21 is 85%, > 21 is 15%. In myopic patients, 15% of patients had POAG, 1% with ACG. Conclusion: Glaucoma, one of the leading causes of irreversible blindness in the adult population worldwide, is a progressive optic neuropathy. Primary open angle glaucoma (POAG) is the most commonly reported type of glaucoma in population based prevalence studies worldwide. Elevated intraocular pressure is a well-known major risk factor for POAG.